2013
DOI: 10.1177/1538574413503564
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Medical Complications and 30-Day End points After Carotid Artery Stenting

Abstract: With the extensive use of carotid artery stenting (CAS) surgeries, scholars are paying more attention to the safety and efficiency of CAS. Our study aims to analyze the clinical efficiency, safety, and technical feasibility of CAS surgery in the treatment of carotid artery stenosis. A total of 379 cases of CAS were collected and retrospectively analyzed. The outcomes were summarized according to decrease in stenosis extent, incidence of early complications after procedure, 30-day end point events, and the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…In agreement with the studies by Schlüter et al [12] and Wang et al [13], we observed a higher short-term complication rate in diabetic patients. Potential explanations for this finding include platelet dysfunction and a higher coagulable state in diabetic patients; increased production of hyperreactive thrombocytes has been shown in diabetics [14]; increase in tissue factor procoagulant activity [15]; increased plasminogen activator inhibitor (PAI)-1 [16], or enhanced complement-fibrinogen binding activity leading to a prothrombotic clot with thinner fibers [17,18].…”
Section: Discussionsupporting
confidence: 83%
“…In agreement with the studies by Schlüter et al [12] and Wang et al [13], we observed a higher short-term complication rate in diabetic patients. Potential explanations for this finding include platelet dysfunction and a higher coagulable state in diabetic patients; increased production of hyperreactive thrombocytes has been shown in diabetics [14]; increase in tissue factor procoagulant activity [15]; increased plasminogen activator inhibitor (PAI)-1 [16], or enhanced complement-fibrinogen binding activity leading to a prothrombotic clot with thinner fibers [17,18].…”
Section: Discussionsupporting
confidence: 83%